New Addition, Different Habitats, Distribution Range and Diversity of Genus Strobilanthes (Acanthaceae) in Sri Lanka - Nilanthi, R.M.R.; Rajathewa, R.A.M.P.M.; Jayawardana, N. (Department of Forestry and Environmental Science University of Sri Jayewardenepura, 2021)
Strobilanthes Blume (Acanthaceae) is one of the largest genera in the flora of Sri Lanka and is most interesting for its diversified habits, gregarious occurrence, and elegant flowering. Approximately 450 Strobilanthes species are widely distributed in the tropical and subtropical parts of Asia. Wood recognized 30 Strobilanthes species in Sri Lanka in 1994. Later, three species were added, Strobilanthes willissi in 2000, S. cordofolia in 2014 and S. medahinensis in 2021. Strobilanthes reptans is reported for the first time from Sri Lanka. With this new addition, Sri Lanka consists of 34 Strobilanthes species. Extensive plant explorations were conducted across the entire distribution range of the genus Strobilanthes in Sri Lanka, covering 21 administrative districts from September 2005 to April 2021. The genus Strobilanthes grow from 100 m to 2,500 m, in an extensive range of different habitats. We could record S. gardneriana, critically endangered possibly extinct species from Hantana at 1,330 m elevation in 2020 after 1927 and critically endangered species, S. rhytisperma from Gendagala in 2019 after after 1971. Species distributions are more expansive with increasing altitude. The extended distributional record for many species of Strobilanthes could be found. However, several species were not found in their type locality. We could see them at other locations. Therefore necessary conservation measures should be taken to conserve such diversity and overcome threats.
Keywords: Gregarious, altitudes, undergrowth, locality, exploration